Language Shift of Krama to Bahasa Indonesia among Javanese Youths and it’s Relation to Parents’ Social Class - Winarti, Oktifani (Jurnal Studi Komunikasi, 2018)
In Javanese tradition, during every encounter, the communicator had to be aware with the other people social standing to be able to choose the appropriate style of conversation based on the relationship. This article is trying to explore how the phenomenon of Javanese language shift happened in Indonesia as well as too see if social class would play important role in it. As social changes might probably bring differences to language use as it has direct influence from the social status coming from Weber’s social class theory. The conclusion of this article, author found a threat for krama as Indonesia’s language heritage that might vanish. In the context of family communication, future research might want to try to see if parental social class can help the generation to maintain a nation’s language heritage regardless of their social class stratification.